GSM Based Garbage Monitoring System - Surbhure Swapnil; Muntode, Nazirkar Nagesh; KATARIA, Khartude Akash; KATARIA, Sangle Nilesh; KATARIA, Dr. Avchat H. S (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In the recent times, Urbanization has increased tremendously. At the same phase there is an increase in waste production. Waste management has been a crucial issue to be considered and efforts using traditional bins as currently used in City has remained inefficient in managing garbage even though helps in garbage collection. This project is a way to achieve this good cause. In this project, a smart bin built and installed in a housing uses a microcontroller-based platform Arduino Uno board which is interfaced with GSM, a pair of level sensor (laser with a photocell) and a stepper motor modelled compressor. The housing is to isolate the garbage from the environment. The laser with a photocell is placed at the top of the bin which will measure the stature of the bin, the compressor connected to the circuit is positioned just at the top level of the bin for compression. The Arduino is programmed in such a way that as the dustbin is being filled, the sensor is activated to monitor the fill level. Once the garbage reaches the positioned level of the sensor, a message will be sent to the circuit which will trigger the compressor to compress and finally an alert through the GSM will be sent to the waste management authority for bin emptying when the bin gets filled up again after the compression. Once the bin is emptied, people can reuse the dustbin. Once these smart bins are implemented on a large scale, by replacing our traditional bins present today, waste can be managed efficiently as it will reduce the interaction of waste with the environment, increases the volume of bins for garbage collection through the compression feature, avoids unnecessary lumping of wastes on roadside. Foul smell from these rotten wastes that remain untreated for a long time, due to negligence of authorities and carelessness of public may lead to long term problems. Breeding of insects and mosquitoes can create nuisance around promoting unclean environment, which is a great blow City is facing today.